Insights from poverty maps for development and food relief program targeting: an application to Malawi - Benson, Todd (International Food Policy Research Institute, 2006)
Poverty mapping applies models of household welfare developed from detailed household consumption and expenditure surveys to the extensive but less detailed data from national censuses. A poverty map for Malawi, developed by drawing upon information from the 1997–98 Malawi Integrated Household Survey with the 1998 Malawi Population and Housing Census, provides aggregate estimates of household welfare and poverty at a highly disaggregated level—down to the level of local government wards. Given the close association between welfare and food security in most Malawi households, such a detailed poverty map can be of considerable value to development and relief organizations, as they plan and target activities to improve the ability of poor households to cope with food scarcity. This paper assesses the value of the Malawi poverty map with reference to two activities of the World Food Programme (WFP) in Malawi: the Food for Assets and Development (FFASD) public works program and the Vulnerability Analysis and Mapping (VAM) food insecurity information generation system. First, the poverty targeting efficiency of the FFASD program is evaluated using the poverty map to determine whether the FFASD projects are preferentially located in areas where disproportionate numbers of the poor are found. This is done in part by comparing the poverty targeting efficiency of the WFP program to that of the Malawi Social Action Fund Public Works Programme projects. Second, WFP employs the VAM methodology to determine how and where to employ its resources from year to year. The potential value of the poverty map as a component of the VAM process in Malawi is then considered. The results indicate that the poverty map is an effective and objective way to geographically target projects and programs on a poverty basis in Malawi. In assessing household vulnerability to food insecurity, the poverty map serves as a useful proxy indicator of spatial variability in the ability of the population to cope with food scarcity. Poverty maps, in those countries were they are available, should be a privileged data source for undertaking any national vulnerability analyses. However, the poverty map needs to be used with complementary data to better understand the risks households face that might result in food scarcity and the actual mechanisms households use to cope with such stresses.